Autonomy or Nonautonomy of Gene Effects in Mosaics - Tokunaga, Chiyoko (1972)
The dominant autosomal gene Msc (Multiple sex combs) of Drosophila causes the appearance of sex combs on the second and third legs and a reduction of size of sex combs on first legs. The effect of Msc was studied in mosaic flies in which non-Msc spots were present on a Msc background. Mosaics were due to somatic crossing-over induced by x-rays. Analysis of mosaics suggested autonomy of the action of Msc, provided that the somatic crossing-over occurs less frequently proximally to the Msc locus than distally. This unusual ratio of somatic crossing-over was confirmed by a separate experiment with the gene Kinked, whose locus is very close to Msc.